Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 4758960 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "Geometry POLYGON((-80.859374 -3.864254,-76.992187 9.968850,-74.355468 13.752724,-58.535156 13.410994,-28.828124 -6.839169,-33.222656 -22.593726,-79.628906 -20.632784,-80.859374 -3.864254))", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 4758960 records from 351 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005603-150528172251762/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences